The energy consumption and pellets' characteristics in the co-pelletization of oil cake and sawdust. Issue 23 (16th February 2016) - Huang, Z. L.; Li, H.; Yuan, X. Z.; Lin, L.; Cao, L.; Xiao, Z. H.; Jiang, L. B.; Li, C. Z.
Abstract : Improvement of the co-pelletization of biomass (cedarwood and camphorwood) and oil cake was carried out in the present work. Abstract : Improvement of the co-pelletization of biomass (cedarwood and camphorwood) and oil cake was carried out in the present work. The characteristics of the raw materials were determined by chemical and physical analysis. The co-pelletization process was studied by quantifying the energy consumption of compaction and extrusion processes. The physical properties of the pellets, including moisture adsorption, pellet energy density and hardness, were also determined. The blending of biomass with oil cake would increase the density of the pellets, and thus reduce their costs during production, transport and storage. The energy consumption of compaction decreased upon increasing the castor bean cake content, while the energy consumption of extrusion and the pellets' energy density showed the opposite tendency. Moreover, the maximum compression force and hardness increased with the increase in the blend ratio of CAS (castor bean cake). This thermal analysis suggests that adding CAS can enhance char combustion and can lead to greater reactivity during char combustion. 10–20% of castor bean cake by mass would be a suitable proportion in co-pelletization with biomass, in terms of energy consumption and the pellet properties.